2022
DOI: 10.3390/w14203243
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis Mechanism and Health Risk Assessment of High Boron Water in the Zhaxikang Geothermal Area, South Tibet

Abstract: The natural discharge of geothermal water containing harmful components affects the water quality of the surrounding environment and brings security risks to drinking water safety. The geothermal water in Tibet is characterized by high boron content, but the water pollution caused by the discharge of this high boron geothermal water is not clear. In this study, we collected geothermal water and surface water from the Zhaxikang geothermal system in southern Tibet to investigate the causes of high boron geotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Moreover, hybrid systems can use either freshwater or geothermal fluids for cooling, where the latter would theoretically alleviate the water footprint. Notwithstanding, water quality remains a disturbing issue; hot water pumped from underground reservoirs (usually in steel well casings) often contains high levels of sulfur, salt, and other toxic minerals, above environmental standards (Baysal and Gunduz 2016 ; Li et al 2022b ), which might over time corrode the casings and then seep through to contaminated pristine groundwater resources. Correspondingly, these toxic chemicals are present in wastewater discharged to nearby aquatic milieu, thereby adversely impacting florae and faunae, and ultimately human health.…”
Section: A Well-balanced Succinct Appraisal Of Some Existing New Gene...mentioning
confidence: 99%
“…Moreover, hybrid systems can use either freshwater or geothermal fluids for cooling, where the latter would theoretically alleviate the water footprint. Notwithstanding, water quality remains a disturbing issue; hot water pumped from underground reservoirs (usually in steel well casings) often contains high levels of sulfur, salt, and other toxic minerals, above environmental standards (Baysal and Gunduz 2016 ; Li et al 2022b ), which might over time corrode the casings and then seep through to contaminated pristine groundwater resources. Correspondingly, these toxic chemicals are present in wastewater discharged to nearby aquatic milieu, thereby adversely impacting florae and faunae, and ultimately human health.…”
Section: A Well-balanced Succinct Appraisal Of Some Existing New Gene...mentioning
confidence: 99%
“…The results of Li's (2022) research on the health risk assessment of boron content in the mountains of Southern Tibet revealed that the boron content in geothermal water in the study area reached 42.36 mg / L, far exceeding the drinking water limit set by the World Health Organization (0.5 mg / L). Health risk assessments to drinking water in the study region showed that the hazard index (HI) of drinking water in mixed regions was higher than 1 (with an average of 1.594 for children and 1.366 for adults), indicating that children are at high health risk.…”
Section: Methodsmentioning
confidence: 76%
“…Health risk assessments to drinking water in the study region showed that the hazard index (HI) of drinking water in mixed regions was higher than 1 (with an average of 1.594 for children and 1.366 for adults), indicating that children are at high health risk. higher health risks compared to adults (Li et al, 2022).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations